PENGARUH CAR, RORA, NPM, OEOI, LDR TERHADAP RETURN BPR (BANK PERKREDITAN RAKYAT) DI JATENG - Elisabet Stefani Novia K, 11.05.52.0011; Susilowati, Yeye (Students Journal of Accounting and Banking, 2015)
The aim of this study is to examine and analyze the influence of CAR, RORA, NPM, OEOI, LDR on returns banking BPR. This research was conducted from 2011 to 2013 in the Rural Bank in Central Java. Data were analyzed using multiple regression test with the classical assumption. Results of the study: (1) There is a positive effect CAR to return the banking BPR. (2) There is a positive effect RORA on the return of the banking BPR. (3) There is a positive effect NPM on the return of the banking BPR. (4)There is a positive effect OEOI on the return of the banking BPR. (5) There is no effect LDR on the return of the banking BPR.Keywords: CAR, RORA, NPM, OEOI, LDR, Return BPR